2011
DOI: 10.1016/j.snb.2010.12.024
|View full text |Cite
|
Sign up to set email alerts
|

Humidity sensors based on ZnO/TiO2 core/shell nanorod arrays with enhanced sensitivity

Abstract: Highly aligned arrays of ZnO/TiO(2) core/shell nanorods were fabricated on glass substrates by hydrothermal growth of ZnO nanorods cores followed by the deposition of anatase TiO(2) shells in a sol-gel process. The characterization of these composite materials with scanning electron microscopy (SEM), Raman spectroscopy, X-ray diffraction (XRD), energy dispersive X-ray spectroscopy (EDX) and transmission emission microscopy (TEM) points to the formation of crystalline ZnO nanorod cores that are coated with anat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
67
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 142 publications
(67 citation statements)
references
References 33 publications
0
67
0
Order By: Relevance
“…In the beginning, at pretty low humidity, a few water molecules are adsorbed on the film surface, which correspond to the chemisorption and primary physisorption layers. In these preliminary layers, hydroxyl groups are formed by dissociation mechanism [13,37]. Later, with rising humidity levels, more vapors are adsorbed on the surface and subsequent physisorption layers are formed.…”
Section: Device Characterizationmentioning
confidence: 99%
“…In the beginning, at pretty low humidity, a few water molecules are adsorbed on the film surface, which correspond to the chemisorption and primary physisorption layers. In these preliminary layers, hydroxyl groups are formed by dissociation mechanism [13,37]. Later, with rising humidity levels, more vapors are adsorbed on the surface and subsequent physisorption layers are formed.…”
Section: Device Characterizationmentioning
confidence: 99%
“…The structure is uniform and surface area is also increase by increasing the dopant concentration. Gu et al also reported on the ZnO nanorods [14]. They have obtained nanorods structure using hydrothermal grown method.…”
Section: Zno Nanostructuresmentioning
confidence: 99%
“…ZnO, (4) SnO 2 , (5) B 2 O 3 , (6) and ZrO 2 , (7) have proven particularly effective, due to their superior mechanical, chemical, and thermal stability. (8) A variety of techniques and devices are used for the measurement of humidity, including impedance, (9) capacitance, (10) optics, (11) resistance, (12) and the quartz crystal microbalance.…”
Section: Introductionmentioning
confidence: 99%